Planejamento de marketing em bibliotecas universitárias: aplicação na biblioteca do ICED/UFPA - SANTOS, Karoline Grasielly Fernandes dos (2017)
Discussions about the application of marketing in university libraries have become popular, as institutions seek ways to renew themselves and reach their goals, in order to satisfy the final customer. In this context, from the experiences of internship and the debates promoted during extension activities carried out at Instituto de Ciências da Educação (ICED) of the Universidade Federal do Pará (UFPA), came the proposal for this research, wich aims to describe marketing planning in the ICED Library. Specifically, objectives to subsidize the strategic planning, and to follow and identify the stages of marketing planning. Uses participant observation to collect data and content analysis for its treatment. Describes the methods applied by the library in marketing planning, which uses triangulation on various techniques to collect and analyze data (documentary research, observation, interviews, focus group and benchmarking), making it possible to verify the convergence of the information found. Results in a methodological description for the construction of the marketing plan and its constituent elements: the environmental analysis, the segmentation of the public, the definition of the positioning, the strategies and the marketing mix (Products and services, Place, Price and costs, Promotion and Communication) and the action plan. Concludes that marketing planning in university libraries enables a more accurate diagnosis of the users' vision of the information unit, the identification of the needs of each distinct group of users and the definition of a positioning that guides the activities and actions developed for each planned period.